COMPARATIVE STUDY OF INDICATORS OF MALADJUSTED PSYCHOSOCIAL BEHAVIOR AMONG HIGH SCHOOL STUDENTS WITH HIGHER AND LOWER PROPENSITY TO BULLYING BEHAVIOR: ESTUDIO COMPARATIVO DE INDICADORES DEL COMPORTAMIENTO PSICOSOCIAL DESAJUSTADO ENTRE ESTUDIANTES DE SECUNDARIA CON MAYOR Y MENOR PROPENSIÓN A LA CONDUCTA DE BULLYING - Sánchez Carlessi, Héctor Hugo (2024)
Introduction: Bullying is harmful behavior in school contexts, affecting students' lives. Objective: To identify and compare indicators of maladjusted behavior in students with different propensities to bullying. Methodology: This descriptive and quantitative study used surveys and a comparative followed by correlational design to assess maladjusted behaviors (stress, low self-esteem, incivility, family maladjustment, propensity to violence) in secondary students from Lima and Callao. The non-probabilistic sample included 1345 first and second-year students, divided into two groups based on their bullying propensity (high -Group E- and low -Group C-). Scales from the INDACPS inventories and the Bullying Propensity Scale (BPS) were applied, analyzing data with SPSS v.25 and Jamovi. Differences between groups were assessed using the Mann-Whitney U test, and variable correlation was determined using Spearman's correlation. Results: Group E had higher levels of stress, low self-esteem, incivility, family maladjustment, and propensity to violence, with statistical significance (p<0.001) compared to Group C. Statistically significant correlations were found between the propensity to bullying and these indicators, being stronger in the total sample (p<0.001). Additionally, significant gender differences were observed in stress, low self-esteem, family maladjustment, and propensity to violence, but not in incivility and bullying propensity. Conclusion: Students with a higher propensity to bullying exhibit higher levels of stress, low self-esteem, incivility, family maladjustment, and propensity to violence, underscoring the importance of comprehensive interventions.